School dropout in professional education in the Amazon: : a literature review - Anic, Cinara Calvi; Silva , Romilson Alves da (Revista Labor, 2021)
School dropout is a longstanding problem in Brazilian education. The term dropout in the literature refers to several situations, such as school dropout, temporary departure of the student from the institution, among others. In the case of Professional Education, there is a contrast between the increasing number of openings and the continuing high dropout rates in the courses. This research is part of a master's research project that aims to investigate the perspectives for dealing with students dropouts in professional education at a local school in the State of Pará. As a part of this research, we present, in this study, the results of a literature review on the subject of school dropout in professional education in the Amazon, based on a bibliographical survey in two databases. The results showed a great variety of research regarding the level of education and modalities studied, but few studies focused on the context of professional education. The themes studied deal mostly with the identification of the various factors that lead students to drop out, including individual and institutional factors. Moreover, in line with recent review studies on school dropout, we found a lack of understanding about the concept of dropout. It is hoped that these results can support new research that focuses on understanding the dropout issue in its various dimensions, especially those directed to vocational education, given the demands related to the world of work that are presented in contemporary times.